Developments and Applications of Additive Manufacturing in the Automotive Industry - Kazeem A. BELLO; Adeniyi O. ADESINA; Lukman A. OPEYEMI; Solomon O. UVIASE; Francis O. BOROKINNI; Friday ONUH; Tunde O. OGUNDANA; Adebayo I. OLUMOROTI (FUDMA Journal of Engineering and Technology, 2026)
Additive Manufacturing (AM), otherwise known as 3D printing, is transforming the automotive sector by increasing design freedom, decreasing manufacturing costs, and improving efficiency. AM is suitable for rapid prototyping, facilitating a fast track to product development while also minimising material waste. AM also permits the production of lightweight, high-strength parts, allowing for better fuel efficiency and performance of the automobile. Furthermore, AM also enables mass customisation of parts, allowing auto manufacturers to create components for their vehicles based on customer preferences. This technology optimises supply chain logistics by producing spare parts on demand rather than keeping inventory, resulting in cost savings and sustainability. Various methods for AM, such as fused deposition modelling (FDM), selective laser sintering (SLS), and direct metal laser sintering (DMLS), are often used for prototyping, tooling, and end-use parts. A qualitative research design was employed, predominantly by undertaking a thorough literature review into the applications, advantages, challenges, and future perspectives of AM in automotive enterprises. The necessary data that was collected encompassed findings from academic journals and conference papers, as well as industry reports and case studies on Ford, BMW, and General Motors, as well as other emerging technologies. Overall, the findings suggest that AM can improve vehicle production with rapid prototyping, lighter-weight components, mass customisation, cost-effective production, and design flexibility. Nevertheless, the main unforeseen challenges include AM’s high initial cost of production, slow production speed, and no universal and reliable material properties. As AM continues to develop, it will have a major role in streamlining automotive manufacturing, reducing the environmental effects of transportation, and innovating automotive design and production, with the long-term potential to disrupt the automotive sector’s production model.